(untitled) (Research, Society and Development, 2025)
Chagas Disease (CD) has a significant impact on the health of the Latin American population. It primarily affects low-income individuals, people with low levels of education, and residents of rural areas and poor neighborhoods of large urban centers. One-third of affected individuals may develop symptoms that interfere with their lives, reducing their ability to work and leading to discrimination. This restrictive and adverse reality can generate psycho-affective disorders that manifest in social, family, and work relationships. Studies have shown that patients with CD may exhibit psychological changes, both cognitive and related to the perception of well-being, showing an association with depression, sadness, reduced quality of life, higher stress levels, and lower resilience. The present study aims to conduct a literature review of the psychometric assessment of depression, quality of life, and subjective well-being in Brazilian patients with CD. A literature review was conducted based on a search of databases from 2005 to 2023. A total of 158 articles were identified, of which 26 were eligible for analysis. Among the studies that analyzed the psychosocial nature of CD, the majority focused on socio-anthropological issues, using interviews that emphasized socioeconomic, non-measurable, symbolic, and cultural aspects. Few studies have utilized instruments with robust psychometric properties. Advancing knowledge in the psychosocial context requires the use of rigorously validated psychometric tools for the psychological assessment of patients with CD.